2007
DOI: 10.1111/j.1399-0004.2007.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyskeratosis congenita: a genetic disorder of many faces

Abstract: Dyskeratosis congenita (DC) is an inherited syndrome exhibiting marked clinical and genetic heterogeneity. It is characterized by multiple features including mucocutaneous abnormalities, bone marrow failure and an increased predisposition to cancer. Three genetic subtypes are recognized: X-linked recessive DC bears mutations in DKC1, the gene encoding dyskerin, a component of H/ACA small nucleolar ribonucleoprotein particles; autosomal dominant (AD) DC has heterozygous mutations in either TERC or TERT, the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
179
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 70 publications
(102 reference statements)
2
179
0
3
Order By: Relevance
“…Dyskerin, also known as Cbf5, is a predominantly nucleolar protein encoded by the DKC1 gene at Xq28 (Mason et al, 2005;Kirwan and Dokal, 2008). As part of a snoRNA ribonucleoprotein complex, dyskerin catalyses the formation of pseudouridine in ribosomal and certain small RNAs (Filipowicz and Pogacic, 2002).…”
mentioning
confidence: 99%
“…Dyskerin, also known as Cbf5, is a predominantly nucleolar protein encoded by the DKC1 gene at Xq28 (Mason et al, 2005;Kirwan and Dokal, 2008). As part of a snoRNA ribonucleoprotein complex, dyskerin catalyses the formation of pseudouridine in ribosomal and certain small RNAs (Filipowicz and Pogacic, 2002).…”
mentioning
confidence: 99%
“…However, there is now a consensus that telomere length correlates to but does not cause aging in most individuals, with immunosenescence being the most tangible correlate (Effros 2007). Exceptions may be a variety of rare premature aging syndromes, such as dyskeratosis congenita (Kirwan and Dokal 2008) and idiopathic pulmonary fibrosis (Blasco 2005), and some cases of liver cirrhosis (Wiemann et al 2002) and myelodysplastic syndromes (Ohyashiki et al 1994), where mutations in telomere maintenance genes have been identified.…”
Section: What Is Not In the Model?mentioning
confidence: 99%
“…Telomerase is a ribonucleoprotein complex, consisting of human transcriptase reverse transcriptase (hTERT), proteins (hTP1), and RNA template for telomeric DNA synthesis (hTERC) [3]; this complex synthesizes telomeres and stabilizes their length. Mutations in any of these components may result in a rare bone marrow failure syndrome known as dyskeratosis congenita [4].…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase is a ribonucleoprotein complex, consisting of human transcriptase reverse transcriptase (hTERT), proteins (hTP1), and RNA template for telomeric DNA synthesis (hTERC) [3]; this complex synthesizes telomeres and stabilizes their length. Mutations in any of these components may result in a rare bone marrow failure syndrome known as dyskeratosis congenita [4].Telomerase activity was reported to be low in normal human somatic cells [3]. Proliferating cells become senescent when telomeres are short and when there is no telomerase activity.…”
mentioning
confidence: 99%